The fundamentals of safe assets. (April 2020) - Habib, Maurizio Michael; Stracca, Livio; Venditti, Fabrizio
Abstract: We study what makes government bonds a safe asset. Building on a sample of monthly changes in government bond yields in 40 advanced and emerging countries, we analyse the sensitivity of yields to country specific fundamentals interacted with changes in global risk (VIX). We find that inertia (whether the bond behaved as a safe asset in the past) and good institutions foster a safe asset status, while the size of the debt market is also significant, reflecting the special role of the US. Within advanced and emerging markets, drivers are heterogeneous, with external sustainability in particular being relevant for the latter countries after the global financial crisis. Finally, the safe asset status does not appear to depend on whether the change in global risk is driven by financial shocks rather than by US monetary policy.